2000
DOI: 10.1046/j.1523-1755.2000.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

ACE genotype and ACE inhibitors induced renoprotection in chronic proteinuric nephropathies1

Abstract: In nondiabetic proteinuric nephropathies, the ACE I/D polymorphism does not predict disease progression, but is a strong predictor of ACE inhibition-associated renoprotection in that proteinuria, DeltaGFR, and progression to ESRD are effectively reduced in patients with the DD, but not in those with the II or ID genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 18 publications
4
47
1
2
Order By: Relevance
“…This differential response to ACE inhibitor treatment was also observed in the EURODIAB Controlled Trial of Lisinopril in IDDM [5]. Curiously, while the D allele has been linked with higher ACE activity [6], several studies have indicated that the DD genotype could be associated with better response to the anti-proteinuric effect of ACE inhibitors in patients with diabetic nephropathy [75] and other renal diseases [76]. With these counter-intuitive findings, the precise manner in which the ACE genotype modifies response to ACE inhibitors remains unresolved.…”
Section: Discussionmentioning
confidence: 67%
“…This differential response to ACE inhibitor treatment was also observed in the EURODIAB Controlled Trial of Lisinopril in IDDM [5]. Curiously, while the D allele has been linked with higher ACE activity [6], several studies have indicated that the DD genotype could be associated with better response to the anti-proteinuric effect of ACE inhibitors in patients with diabetic nephropathy [75] and other renal diseases [76]. With these counter-intuitive findings, the precise manner in which the ACE genotype modifies response to ACE inhibitors remains unresolved.…”
Section: Discussionmentioning
confidence: 67%
“…These different trends were not explained by differences in patient characteristics that were similar between different genotypes. Of note, finding that BP control was also similar between groups suggests that different outcomes reflected a specific effect of the ACE I/D polymorphism on intrinsic kidney responsiveness to ACE inhibitor therapy (19). Consistently, a smaller study in patients with IgA nephropathy found more treatment-induced proteinuria reduction in those with the DD than in those with the ID or II genotype (55).…”
Section: Ace Inhibitorsmentioning
confidence: 76%
“…One randomized, double-blind, placebo-controlled, clinical trial, the Ramipril Efficacy In Nephropathy (REIN) study (34), was formally designed to test whether glomerular protein traffic and its modification by ACE inhibitor therapy influenced chronic renal disease progression. This study prospectively evaluated the relationships between ACE I/D polymorphism and kidney function loss by serial GFR measurements by goldstandard techniques in patients with different nondiabetic renal diseases (19). Data in 212 genotyped patients showed a similar rate of GFR decline and incidence of ESKD in different ACE I/D subgroups, an effect, however, that was the result of different response to ACE inhibitor and conventional therapy in considered groups.…”
Section: Nondiabetic Renal Diseasementioning
confidence: 99%
“…12,[15][16][17] However, this relationship is controversial in some studies. 18,19 It has been suggested that DD genotype can have some impact on the rate of renal function loss, but that the impact of the genotype can be obscured by other risk factors. 20 Unfortunately, the contrasting studies are hard to compare, because of the heterogeneity in ethnic background, possible interactions with other genetic or environmental renal risk factors, and mostly small sample size.…”
Section: Discussionmentioning
confidence: 99%